Comrade Tito, All of Us Are – You - Sorel, Sanjin (Poznańskie Studia Slawistyczne, 2013)
The article describes different ways of depicting Josip Broz Tito in poems which embody socialistic values. The notion of the Government relies on the idea of the abscence, and the exact abscence requires the image in order to be effective. This is the key role of poetry, which conveyed the constructs of both individual and social illusion.